Amphiphilic Ferrocene-Containing PEG Block Copolymers as Micellar Nanocarriers and Smart Surfactants - Alkan, Arda (Langmuir : the ACS journal of surfaces and colloids, 2017)
An important and usually the only function of most surfactants in heterophase systems is stabilizing one phase in another, for example, droplets or particles in water. Surfactants with additional chemical or physical handles are promising in controlling the colloidal properties by external stimuli. The redox stimulus is an attractive feature; however, to date only a few ionic redox-responsive surfactants have been reported. Herein, the first nonionic and noncytotoxic ferrocene-containing block copolymers are prepared, carrying a hydrophilic poly(ethylene glycol) (PEG) chain and multiple ferrocenes in the hydrophobic segment. These amphiphiles were studied as redox-sensitive surfactants that destabilize particles as obtained in miniemulsion polymerization. Because of the nonionic nature of such PEG-based copolymers, they can stabilize nanoparticles even after the addition of ions, whereas particles stabilized with ionic surfactants would be destabilized by the addition of salt. The redox-active surfactants were prepared by the anionic ring-opening polymerization of ferrocenyl glycidyl ether, with PEG monomethyl ether as the macroinitiator. The resultant block copolymers with molecular weights (Mn) between 3600 and 8600 g mol-1 and narrow molecular weight distributions (Mw/Mn = 1.04-1.10) were investigated via 1H nuclear magnetic resonance and diffusion ordered spectroscopy, size exclusion chromatography, and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Furthermore, the block copolymers were used as building blocks for redox-responsive micelles and as redox-responsive surfactants in radical polymerization in miniemulsion to stabilize model polystyrene nanoparticles. Oxidation of iron to the ferrocenium species converted the amphiphilic block copolymers into double hydrophilic macromolecules, which led to the destabilization of the nanoparticles. This destabilization of nanoparticle dispersions may be useful for the formation of coatings and the recovery of surfactants